Oral manifestation in systemic lupus erythematosus: a case report / Wan NurHazirah Wan Ahmad Kamil and Nor Nazaliza Basri. - Wan Ahmad Kamil, Wan NurHazirah; Basri, Nor Nazaliza (2019)
Systemic lupus erythematosus (SLE) is a chronic autoimmune inflammatory disease with diverse clinical manifestations affecting several organs such as the brain, lungs, kidneys, heart, blood vessels, muscles and skin. Oral manifestations might be the first sign and symptoms of SLE. Hence, this paper describes a 58-year old lady whom oral lesions were the first manifestation of SLE disease. The oral manifestations and management of this patient was discussed.